Module Development of Teaching Materials for Explanation Text Materials in Indonesian Language Subjects to Increase the Reading Interest of Students in Class V Elementary School - Tsalis, Masruro Rahma; Fitriyani, Fitriyani (Continuous Education: Journal of Science and Research, 2023)
Modules are learning materials that are designed in accordance with the applicable curriculum and are intended to achieve predetermined competency standards. Modules can be used to support subject matter, as well as make learning more interesting and fun. This study aims to develop a teaching material module for explanatory text material to increase students' interest in reading, to find out the assessments of three experts and the opinions of teachers and fifth grade elementary school students. In this study using the type of learning design development research or R&D using the ADDIE module. The subjects of this study consisted of three experts (materials experts, linguists and media experts) as well as fifth grade elementary school students. The instrument used in this study was a questionnaire given to three experts obtained through research results, namely qualitative data which was analyzed using quantitative data in the form of numerical data. The results of this study are, to produce a module product of explanatory text material that meets very good criteria with the acquisition of an average validation score from three validators obtaining a value of 99% with a very feasible category to use, and a practicality level of 90% is in the very practical criteria and the level of effectiveness with an average of 91.8% is in the very effective category. The teaching material module of explanatory text material is feasible, practical and effective for use in learning.